2017
DOI: 10.1038/s41598-017-07190-z
|View full text |Cite
|
Sign up to set email alerts
|

Mining novel starch-converting Glycoside Hydrolase 70 enzymes from the Nestlé Culture Collection genome database: The Lactobacillus reuteri NCC 2613 GtfB

Abstract: The Glycoside hydrolase (GH) family 70 originally was established for glucansucrases of lactic acid bacteria (LAB) converting sucrose into α-glucan polymers. In recent years we have identified 3 subfamilies of GH70 enzymes (designated GtfB, GtfC and GtfD) as 4,6-α-glucanotransferases, cleaving (α1 → 4)-linkages in maltodextrins/starch and synthesizing new (α1 → 6)-linkages. In this work, 106 putative GtfBs were identified in the Nestlé Culture Collection genome database with ~2700 genomes, and the L. reuteri N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…An inventory of the GH70 enzymes present in the Nestlé Culture Collection genome database resulted in identification of 106 putative GtfB enzymes. Only seven of these GtfB-like protein sequences displayed further differences in motifs II and IV (Gangoiti et al, 2017c), namely at the same positions (1029, 1137 and 1140, Gtf180 numbering) as observed for L. fermentum GtfB 4,3-α-GTase (see Fig. 2C, D for more details).…”
Section: Lactobacillus Reuteri Ncc 2613 Gtfb 46-α-glucanotransferasementioning
confidence: 58%
See 1 more Smart Citation
“…An inventory of the GH70 enzymes present in the Nestlé Culture Collection genome database resulted in identification of 106 putative GtfB enzymes. Only seven of these GtfB-like protein sequences displayed further differences in motifs II and IV (Gangoiti et al, 2017c), namely at the same positions (1029, 1137 and 1140, Gtf180 numbering) as observed for L. fermentum GtfB 4,3-α-GTase (see Fig. 2C, D for more details).…”
Section: Lactobacillus Reuteri Ncc 2613 Gtfb 46-α-glucanotransferasementioning
confidence: 58%
“…α-GTase(Kralj et al, 2011;Leemhuis et al, 2013a;Bai et al, 2015), the L. fermentum 4,3-α-GTase(Gangoiti et al, 2017b), and the L. reuteri NCC 2613 GtfB 4,6-α-GTase(Gangoiti et al, 2017c).…”
mentioning
confidence: 99%
“…Lactobacillus reuteri NCC 2613 GtfB (Gangoiti, van Leeuwen, Meng, et al 2017 was found to encode two GH70 enzymes (named DSRE and BRS-A) specialized in (a1!2) transglycosylation from sucrose to a dextran acceptor substrate (Brison et al 2012;Passerini et al 2015). The gluco-oligosaccharides containing (a1!2) linkages synthesized by L. mesenteroides NRRL B-1299 DSRE were found to be highly resistant to the action of digestive enzymes in both humans and animals (Valette et al 1993).…”
Section: Dextranmentioning
confidence: 99%
“…In recent years, novel GH70 enzymes inactive on sucrose, but displaying clear disproportionating activity on starch/ maltodextrin substrates, have been identified (Table 3) (Gangoiti et al 2015;Gangoiti, Pijning, and Dijkhuizen 2016;Gangoiti, Lamothe, et al 2017;Gangoiti, van Leeuwen, Gerwig, et al 2017;Gangoiti, van Leeuwen, Meng, et al 2017;Kralj et al 2011;Leemhuis, Dijkman, et al 2013). Regarding their substrate specificity, these starch-converting GH70 enzymes resemble GH13 family enzymes also acting on starch-like substrates, however, they share higher amino acid sequence similarity with GS from the GH70 family.…”
Section: Dextranmentioning
confidence: 99%
See 1 more Smart Citation